The analysis of project-based learning models implementation on student motivation and learning achievement - Amara Mery Athaya; Mira Kusmiati; M. Azhar Faturachman (Curricula)
Learning activities are now centered not only on teachers but also on students who actively participate in the process. Learning motivation needs to be developed in students to achieve high learning outcomes. There are several learning models that teachers can use in the teaching process, one of which is project-based learning. This learning model is a model that guides students to engage in a project collaboratively and provides them with opportunities to develop themselves based on their real experiences. This study aims to analyze the implementation of the project-based learning model on student motivation and learning achievement in the environment of one of the Vocational High Schools in the Lembang area. The research method used in this study is a qualitative approach using the interview method. The results of the study show that this learning model increases student participation in learning so that students are encouraged to have motivation and achieve in getting good project results.